Pengaruh Beban Kerja Dan Lingkungan Kerja Terhadap Turnover Karyawan Di PT Tunas Toyota Cakung: The Impact of Workload and Work Environment on Employee Turnover at PT Tunas Toyota Cakung - Kusmawan, Novit Ari; Warsono, Warsono; Syabrinildi, Syabrinildi (CV Warnak Johanna Nusantara, 2025)
PT Tunas Toyota Cakung understands that there are imperfections in the company's performance caused by declining productivity and high employee turnover in several production lines. This can interfere with the business in achieving the company's goals in accordance with the company's vision and mission. The purpose of this study is to find out whether the influence of workload and work environment on employee turnover in the workshop division of PT Tunas Toyota Cakung. This study uses quantitative data with data collection carried out by distributing questionnaires to 50 respondents of PT Tunas Toyota Cakung. The sampling technique in this study is a saturated sample, where all populations are used as a sample of 50 respondents. This study uses several tests, namely the data quality test, the classical assumption test, the hypothesis test, and the last one there is the determination coefficient (R2) test. The results of the test were found that simultaneously the workload and work environment on employee turnover in the workshop division of PT Tunas Toyota Cakung with a value of Fcalung (42,462) > Ftabel (3,195), while in the partial variable test, the significance value of the workload variable <0.001<0.05 and the work environment was 0.023<0.05 which means that these two variables had a significant effect on turnover employees in the workshop division of PT Tunas Toyota Cakung..